Approximate methods for the solution of the equation of acoustic wave propagation in horns - ZAMORSKI, Tomasz; WYRZYKOWSKI, Roman (Archives of Acoustics, 1981)
In practice, there are acoustic horns designed for which the equation of wave propagation has no exact solution of compact form. The need, therefore, arises for approximate solutions, to be used. Accordingly, this investigation sought optimum methods for an approximate solution of the wave equation of a horn. It was assumed that the optimum method should combine the requirement of relatively little time-consuming calculation and the possibility of physical interpretation of the approximate formulae obtained. It was found that the WKB approximation which is recommended in the literature and has been taken directly from quantum mechanics, in general does not satisfy these requirements, and in addition it cannot be used at all in some cases. Therefore, another two approximate methods were developed and their properties analyzed.